Explaining the Limited Effectiveness of Legalistic “Remedies” for Trust/Distrust - Sitkin, Sim B.; Roth, Nancy L. (Organization Science, 1993)
Organizations frequently adopt formal rules, contracts, or other legalistic mechanisms when interpersonal trust is lacking. But recent research has shown such legalistic “remedies” for trust-related problems to be ineffective in restoring trust. To explain this apparent ineffectiveness, this paper outlines a theory that distinguishes two dimensions of trust—task-specific reliability and value congruence—and shows how legalistic mechanisms respond only to reliability concerns, while ignoring value-related concerns. Organizational responses to employees with HIV/AIDS are used as a case illustration that supports the theory's major propositions. The paper concludes with an agenda for future research.